EXPLORING THE TECHNICAL COMPETENCY OF TECHNICAL AND VOCATIONAL TEACHERS IN SOUTH-EAST NIGERIA: IMPLICATION FOR THE SUSTAINABILITY OF TVET PROGRAMS - Onaga, Paul (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
There is growing concern about the sustainability of technical vocational education and training (TVET) in Nigeria. Indeed, several disparate studies have underscored the various constraints of the programs. Little is known about the technical competency of vocational education teachers. The present study examined the technical competency of instructors in the TVET ecosystem with a focus on the link between technical competency and sustainability of TVET in Nigeria. Two hundred fifty-five vocational education teachers pooled from various TVET institutes in the three states participated in the study. They completed a questionnaire measuring technical competency in six dimensions. The result revealed a high technical competence outcome for material and application (75.5%), work planning (71%), practical pedagogy (66.7%), and theoretical instructional strategy (59.4%). Also, the findings indicated a low technical competency for maintenance (15.6%) and students' workshop management (18.1%). The result has implications for the sustainability and development of TVET in Nigeria